Antiviral therapy defiant mixed viral retinitis post hematopoietic allogeneic stem cell transplant - Nadia Gabarin; Rohan Dadak; Mili Roy; Alexander J. Kaplan; Shariq Haider; Dina Khalaf (Clinical Case Reports)
Abstract Cytomegalovirus (CMV) retinitis is an uncommon presentation post allogeneic transplant and can be vision‐threatening. Our case demonstrates the occurrence of polymerase chain reaction (PCR) proven mixed viral retinitis (cytomegalovirus and varicella zoster virus) post allogeneic stem cell transplant despite multiple prophylactic antiviral therapies, including letermovir, and in the documented absence of CMV DNAemia. A 21‐year‐old female with acute myeloid leukemia presented with mixed viral retinitis (cytomegalovirus and varicella zoster virus) post allogenic transplant. This presentation occurred despite ongoing standard prophylaxis for both of these viruses, as well as following two courses of treatment for CMV viremia, with a documented negative CMV PCR in the blood prior to the presentation with retinitis. The patient was treated with intravenous ganciclovir and subsequently transitioned to oral valganciclovir with durable resolution of the retinitis. We report a rare case of mixed viral retinitis occurring despite multiple antiviral prophylaxes including letermovir and with PCR‐documented absence of preceding CMV viremia, in a post‐allogeneic stem cell transplant patient, with PCR of the aqueous fluid demonstrating two viral populations. With very little existing literature on either mixed viral retinitis or CMV retinitis during letermovir prophylaxis, this case expands the literature on both topics. CMV retinitis is an uncommon potentially vision threatening presentation post hematopoietic stem cell transplant, and can occur due to early CMV reactivation, low CD4 count, and delayed CD4 lymphocyte recovery. Letermovir has poor CNS and retinal penetration. This case highlights the need for more research on secondary prophylaxis with letermovir.